Gamifying streaming apps: the use of gamification strategies by video distribution platforms - Rodrigues, Ricardo Pereira (2021)
In the last decade we have witnessed the assertion of streaming platforms as alternative media for content consumption. The recent history of streaming technology has been grounded in a set of progresses that occur almost naturally as Internet connection speeds increase, data packet prices decrease, and both traditional media companies (eg Disney +, HBO; HBO Max), as major technology companies (eg Youtube; Amazon Prime; Apple TV +) begin to offer their content on closed digital platforms competing with streaming market leaders like Netflix. The emergence of these new platforms impacts directly the ecology of traditional television and film industry, disputing with it the attention of viewers who change or reinforce their video content consumption habits. Due to the growth of the number of on-demand video streaming services available, user experience became a key component of this type of apps. Being the use of gamification strategies common in the design of digital media interfaces and services (Zichermann and Cunningham, 2011), they have also been integrated into video streaming platforms. Gamification concerns the use of strategies and elements native to digital games in contexts and environments not related with games (Deterding et al, 2011). Gamification strategies make use of elements like progress bars, badges, points, or other reward systems, levels, challenges, boards, and notification systems. The goal of applying these strategies tends to be to improve users' engagement. Based on a qualitative methodology, having content analysis as primary data collection method, the paper presents an exploratory research of the implementation of gamification strategies by a sample of video streaming providers. The sample is composed by four platforms: Netflix, HBO, Apple TV+ and Disney+. The sampling criteria were being relevant players in the on-demand video streaming segment (Statista, 2019) and being available in Portugal. The content analysis results will be complemented with direct observation resulting from the first-hand experience of the sample. The study aims, in a first stage, to identify and characterize the gamification elements that are present in the streaming distribution platforms; and in a second stage, to compare the identified strategies with the existing research on the gamification structures observed in other digital content distribution platforms, particularly social media (Ferreira, Jorge & Ganito, 2018).